The Morphology of Saturn's Aurorae Observed During the Cassini Grand Finale. Issue 2 (20th January 2020) - Bader, A.; Cowley, S. W. H.; Badman, S. V.; Ray, L. C.; Kinrade, J.; Palmaerts, B.; Pryor, W. R.
Abstract: Cassini's mission exploring the Saturn system ended with the Grand Finale, a series of orbits bringing the spacecraft closer to the planet than ever before and providing unique opportunities for observations of the ultraviolet aurorae. This study presents a selection of high‐resolution imagery showing the aurorae's small‐scale structure in unprecedented detail. We find the main arc to vary between a smooth and a rippled structure, likely indicating quiet and disturbed magnetospheric conditions, respectively. It is usually accompanied by a diffuse and dim outer emission on its equatorward side which appears to be driven by wave scattering of hot electrons from the inner ring current into the loss cone. The duskside is characterized by highly dynamic structures which may be signatures of radial plasma injections. This image set will be the only high‐resolution data for the foreseeable future and hence forms an important basis for future auroral research on Saturn. Plain Language Summary: At the end of its mission, the Cassini spacecraft performed a set of orbits bringing it closer to Saturn than ever before. By passing over the planet's polar regions at such low altitude, its ultraviolet camera could observe Saturn's aurorae in unprecedented resolution. The observations show for the first time the detailed structure of the main auroral arc which varies between a smooth and a rippled shape, likely depending on how quiet or disturbed the plasma near Saturn is. We further find a host of small arcs and blobs near dusk whose origins are not readily explained with the current understanding of how Saturn's aurorae are driven. Diffuse features surrounding the brightest auroral emissions are attributed to hot electrons from the equatorial plane which are scattered such that they can reach Saturn's atmosphere. These observations are of unique quality and invaluable for future auroral studies. Key Points: We present observations of Saturn's ultraviolet aurorae in unprecedented resolution, revealing previously unseen small‐scale features The main aurorae can be smooth or rippled, likely depending on magnetospheric conditions, and multiple parallel arcs are observed near dusk An outer emission is, although variable in brightness, always present and suggested to be driven by hot electrons from the ring current